Wear estimation of hip implants with varying chamfer geometry at the trunnion junction: a finite element analysis. (1st March 2023) - Gutmann, Celine; Shaikh, Numa; Shenoy, B Satish; Shaymasunder Bhat, N; Keni, Laxmikant G; K N, Chethan
Abstract: The hip joint helps the upper body to transfer its weight to lower body. Along with age, there are various reasons for the degeneration of the hip joint. The artificial hip implant replaces the degenerated hip. Wear between the joints is the primary cause of the hip implant becoming loose. The wear can occur due to various reasons. Due to this revision surgery are most common in young and active patients. In the design phase of the implant if this is taken care then life expectancy of the implant can be improved. Small design changes can significantly enhance the implant's life. In this work, elliptical-shaped hip implant stem is designed, and linear wear is estimated at trunnion junction. In this work, a 28 mm diameter femoral head with a 4 mm thick acetabular cup and a 2 mm thick backing cup is used. The top surface taper radiuses are changed. Solid works was used to create the models. Ansys was used to perform the analysis. It was found that as the radius of the TTR decreased, the wear rate decreased. The least wear rate was found in 12/14 mm taper with a value of 1.15E −02 mm year −1 for the first material combination and with a value of 1.23E −02 mm year −1 for the second material combination. In the comparison between the models with 1 mm chamfer and no chamfer, it was found that the wear rate was lower for the models with 1 mm chamfer. When the chamfer was increased (more than 1 mm), the linear wear increased. Wear is the main reason for the loosening of hip implants, which leads to a revision of an implant. It was found that with a decrease in TTR, there was a small increase in the linear wear rate. Overall, the implant with TTR 6 mm and a chamfer of 1 mm was found to have the least wear rate. To validate these results, the implant can be 3D printed and tested on a hip simulator.